ABLUTION BEFORE SLEEP AS A PREVENTIVE THERAPY FOR SLEEP DISORDERS - Masyitoh Chusnan; Fini Fajrini; Noor Noor; Dailami Julis; Nazarwin Saputra; Dadang Herdiansyah (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
Sleep is an important component for maintaining individual health. Insomnia is a common sleep disorder characterized by difficulty initiating or maintaining sleep or both despite the opportunity to do so. In an Elderly Social Service in the Jombang area, 42.5% of respondents experienced sleep disturbances in the form of insomnia and even 2.5 of the total respondents experienced severe insomnia.This study used a literature review of various scientific articles in the last 10 years. There were four journals that stated there was a significant relationship between ablution therapy before going to sleep on sleep disorders. The movement in ablution written in the Book of Thaharah Tarjih Muhammadiyah directly gives calm to the limbs that are washed as well as a calming therapy for those who carry it out. The author suggests that Muslims carry out one of the prophetic traditions, namely ablution before going to bed because in health science it can have a good impact on sleep quality and prevent sleep disorders.